Support vector machine-based sound pressure extrapolation to overcome the finite aperture used in nearfield acoustic holography. Issue 1 (July 2021) - Zhou, Hefeng; Zhao, Yun; Gao, Dongbao; Tian, Zhangfu; Zeng, Xinwu; Jiang, Weikang
Abstract: Sound pressure extrapolation based on support vector machine (SVM) is proposed in order to reduce the reconstruction error in Fourier-based nearfield acoustic holography (NAH) when the aperture is small compared to the source size. The measured pressure on the aperture is introduced into SVM and then a regression model is obtained to extrapolate the sound pressure outside the aperture. Numerical simulations show that the new method allows a relatively accurate and quick reconstruction in comparison with the results using zero-padding and linear predictive border-padding.